Writing Short Stories Through The Habit of Watching Movies - Winarti Winarti; Mutia Febriyana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Students are required to carry out learning, work, and creative activities at home in this era of the covid-19 pandemic because the virus is deemed unsafe even though there is a vaccine that has just been launched, so of course students feel bored because they are at home. To eliminate boredom, students do many things such as playing social media, looking for entertainment on television, cooking, sleeping, reading books, studying, and watching movies from various media such as youtube, television, VCD, etc. This research is associated with writing short stories. The purpose of this study was to determine the habit of watching films for the fourth semester students of the Indonesian Language Education Study Program FKIP UMSU for the 2020-2021 academic year, to determine the ability to write short stories for the fourth semester students of the Indonesian Language Education Study Program FKIP UMSU for the 2020-2021 academic year, to find out writing short stories through the habit of watching movies. The method used is descriptive method. The test for the habit of watching movies used an objective test (multiple choice). The number of tests is 10 items and each item consists of four alternative answers. If correct, the score gets 1 (for the correct answer choice) and a score of 0 (for the wrong answer choice). The test for the ability to write short stories uses an essay test.